2005
DOI: 10.1080/009140390894102
|View full text |Cite
|
Sign up to set email alerts
|

Polyetherketones: Synthesis, Characterization and Antimicrobial Activity

Abstract: Friedel-Crafts polyetherketones were prepared from o-chlorophenol, 1,4-phenylenedioxy diacetylchloride (1,4-PDC), chloroacetyl chloride (CAC), 1,2-dichloroethane (DCE), and dichloromethane (DCM) using anhydrous aluminium chloride (AlCl 3 ) as catalyst and carbon disulfide (CS 2 ) as solvent. These resins were characterized by IR spectroscopy and gel permeation chromatography. Carius method was employed to obtain the percentage of chlorine content in the resins. The kinetic parameters for the thermal behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The azo compound possesses special bonding properties due to the existence of -N=N-group [12] and have alone pair on nitrogen atom and when linked to an aromatic ring carrying an additional donor sites is well suitable for chelation and formed various metal complexes with transition metal ion with unusual structural, magnetic and biological properties. The thiazole functional group played significantly to generate the diversity of certain biological properties such as antibacterial, antiviral and antitubercular activities [13], [15]. The one pot synthesis of some novel derivatives of thiazolo [2, 3-dihydropyrimidinone] possessing [4-methylthiophenyl] moiety and examined their antibacterial and antifungal activities [16].…”
Section: Introductionmentioning
confidence: 99%
“…The azo compound possesses special bonding properties due to the existence of -N=N-group [12] and have alone pair on nitrogen atom and when linked to an aromatic ring carrying an additional donor sites is well suitable for chelation and formed various metal complexes with transition metal ion with unusual structural, magnetic and biological properties. The thiazole functional group played significantly to generate the diversity of certain biological properties such as antibacterial, antiviral and antitubercular activities [13], [15]. The one pot synthesis of some novel derivatives of thiazolo [2, 3-dihydropyrimidinone] possessing [4-methylthiophenyl] moiety and examined their antibacterial and antifungal activities [16].…”
Section: Introductionmentioning
confidence: 99%
“…The Cu 2+ chelated polyurea shows higher zone of inhibition than the other ones due to higher stability constant and may be used in biomedical applications. Patel et al [ 14 ] reported that the synthesis of low molecular weight polymeric resins contains several functional groups in gaining importance to involve the antimicrobial activity. All the synthesized polymers were examined for the antimicrobial activity against bacteria ( Escherichia coli , Bacillus subtilis , and Staphylococcus citreus ), fungi ( Aspergillus niger , Sporotrichum pulverulentum , and Trichoderma lignorum ), and yeast ( Candida utilis , Saccharomyces cerevisiae , and Pichia stipitis ).…”
Section: Introductionmentioning
confidence: 99%